Babymouse. 19, Bad babysitter - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2015)
"Babymouse discovers that babysitting is not as easy as it sounds"--Provided by publisher.
Horn Book
Horn Book, October 2015
2.4
3-6.
3-6
Keywords: Animals -- Comic books, strips, etc -- Juvenile fiction; Babymouse (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Babysitters -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Money-making projects for children -- Comic books, strips, etc -- Juvenile fiction; Animals -- Fiction; Babymouse (Fictitious character) -- Fiction; Babysitters -- Fiction; Cartoons and comics; Humorous stories; Mice -- Fiction; Moneymaking projects -- Fiction; Animals -- Comic books, strips, etc -- Fiction; Babymouse (Fictional character) -- Comic books, strips, etc -- Fiction; Babysitters -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Graphic novels; Humorous graphic novels; Mice -- Comic books, strips, etc -- Fiction; Money-making projects for children -- Comic books, strips, etc -- Fiction; Graphic novels; Humorous fiction